Handbook of Educational Reform Through Blended Learning - Li, Ming; Han, Xibin; Cheng, Jiangang (Springer Nature, 2024)
This open access book provides related theories, methods, strategies, and practical cases for implementing education reform through blended learning in curriculum, program, and institutions in the digital age. It sums up the research and practice achievements of blended learning from different research teams, involving more than 20 experts from educational technology, higher education, vocational education, and education management over the past 20 years. This book recommends relevant policies of blended learning to international organizations and governments in various countries, provides systematic solutions for administrators in institutions to promote educational reform via blended learning, and serves as a reference book for instructors, researchers, and relevant enterprise practitioners.